Community empowerment for environmental and social improvement in Panancangan Village, Lebak, Banten [Pemberdayaan masyarakat dalam rangka peningkatan ekonomi dan sosial di Desa Panancangan, Lebak, Banten] - Puspitasari, Nindya Farah Dwi; Dhewi, Ratna Marta; Zuhairi, Fawzi Rahmadiyan; Juwita, Rakhmini; Prasetyo, Agus; Nurkhalifah, Risma; Suhendi, Suhendi (Buletin Pengabdian, 2024)
Panancangan Village is located in Cibadak Sub-District, Lebak District, Banten Province. Several village residents had professions as oyster mushroom farmers and the results of cultivating these mushrooms could provide residents with an income of IDR 11,000 per kilo. During initial observations, the community empowerment team found that there were two main problems. The first was environmental problem. The environment around the village office looked barren and the air around the village feels very hot during the day. The second was social problem. Lack of residents skills and knowledge in the fields of mushroom management and food packaging, product marketing, and entrepreneurship, causes farmers to only sell their mushrooms in raw form. The objectives of this community service are providing education to village residents to increase environmental conservation awareness and increasing social development through training and education. Method used is through training both non-practical and practical training in plant cultivation and oyster mushroom management, food packaging, marketing, and entrepreneurship. The evaluation results showed that the training was effective and provided positive benefits for environmental and social improvements.